Preditores de burnout e estresse em trabalhadores brasileiros: estudo longitudinal prospectivo com acompanhamento de 2020 a 2023 - Domingues, Gabriel Eduardo (Universidade Federal de São Carlos, 2025)
Introduction: Burnout and stress were highly prevalent among Brazilian workers during the COVID-19 pandemic and may be associated with psychosocial, sociodemographic, and occupational factors. Understanding these factors is crucial for developing effective policies and interventions aimed at protecting workers' health. Objective: This prospective study, which has been following workers for three years since 2020, aims to identify the predictors of burnout and stress symptoms in Brazilian workers from different professional categories. Methods: Study participants were recruited through advertisements in the local press, social media, and invitations sent by email. After applying the eligibility criteria, 1,211 workers were included in the baseline in 2020. The follow-up was conducted until 2023, with 467 workers. The instruments used were: sociodemographic and occupational questionnaire, Copenhagen Psychosocial Questionnaire II-Br (COPSOQ II-Br), and Work Ability Index (WAI). The analyses were conducted using descriptive statistics to characterize the sample and multivariate logistic regression analysis to identify factors associated with the development of burnout and stress symptoms. Results: Age had a protective effect against stress (OR = 0.975; 95% CI = 0.952 - 0.998; p = 0.033) and burnout (OR = 0.956; 95% CI = 0.931 - 0.981; p = 0.001), as did family income (OR = 0.529; 95% CI = 0.314 - 0.891; p = 0.017; OR = 0.485; 95% CI = 0.273 - 0.864; p = 0.014), respectively. On the other hand, the change in workload was associated with an increased risk of stress (OR = 2.271; 95% CI = 1.346 - 3.831; p = 0.002) and burnout (OR = 1.827; 95% CI = 1.033 - 3.232; p = 0.038). Workers in the education sector (OR = 2.874; 95% CI = 1.490 - 5.542; p = 0.002) had an increased risk of burnout compared to other sectors. In addition, fear of COVID-19 infection at work (OR = 1.974; 95% CI = 1.124 - 3.465; p = 0.018) and a diagnosis of anxiety (OR = 3.897; 95% CI = 1.648 - 9.218; p = 0.002) were identified as significant risk factors for burnout. Conclusion: This study highlights the factors associated with the development of burnout and stress symptoms in Brazilian workers in the context of the COVID-19 pandemic. Managing modifiable factors can contribute to the health of workers and the prevention of burnout and stress symptoms.
Predictors of burnout and stress in brazilian workers: a prospective longitudinal study with follow-up from 2020 to 2023
Keywords: Impacto psicossocial; Estresse psicológico; COVID-19; Saúde mental; Saúde ocupacional; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA DO TRABALHO E ORGANIZACIONAL::FATORES HUMANOS NO TRABALHO; 3. Saúde e Bem-Estar; 8. Trabalho Decente e Crescimento Econômico